1999
DOI: 10.1007/s004170050225
|View full text |Cite
|
Sign up to set email alerts
|

Growth of human fetal retinal pigment epithelium as microspheres

Abstract: HFRPE grown on CLF resemble a three-dimensional culture system with high yield of pure cells that can be useful for a wide variety of in vitro studies. Because of their adjustable size, spherical shape, and ability to initiate growth of cells with a high proliferative potential, HFRPE microspheres may be successfully utilized as a source of donor cells for subretinal transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Pigmented epithelial cells can form three-dimensional culture arrangements known as spheroids [3,9,10,12]. These three-dimensional cellular arrangements have been used for cultivation and transfer of ocular cells in vitro.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pigmented epithelial cells can form three-dimensional culture arrangements known as spheroids [3,9,10,12]. These three-dimensional cellular arrangements have been used for cultivation and transfer of ocular cells in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…These three-dimensional cellular arrangements have been used for cultivation and transfer of ocular cells in vitro. The cells within spheroids maintain a high proliferative activity and are resistant to dedifferentiation [3,12]. Biodegradable polymer films have been applied for the incorporation of HFRPE cells [4] and their subsequent formation of spheroids.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19] Human fetal RPE (HFRPE) cells have previously been cultured as microspheres on crosslinked fibrinogen films prior to being transplanted into the subretinal space of rabbits. [29][30][31] It was shown that microspheres of HFRPE could be delivered reproducibly with ease and that donor cells spread from the site of implantation and survived for up to one month. 29 RPE seeded microcarriers could be easily injected into the subretinal space, with the additional advantage of overcoming problems such problems as reflux from injection site which can be noted with simple cell suspensions.…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that microcarriers were well tolerated in vivo . Optimal culture of RPE cells for transplantation necessitates a culture system which produces a high yield of viable cells from an often limited amount of donor tissue 31…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation